Improvement of SRv6 SID structure - Yonglin TANG; Feng LIU (Dianxin kexue)
IPv6-based segment routing (SRv6) is a new technology addressed by IETF in recent years.In draft-ietf-spring-srv6-network-programming,the 128-bit segment identifier (SID) was structured,and how to be processed in one node was described.The SID structure defined by the draft was improved.A field named “network”was defined in the SID to identify different virtual sub-networks.It was also pointed out that the SID list in the segment routing header (SRH) did not carry the “Network”,and only carried the locator,function and argument,which could effectively reduce the requirements of the multi-layer SRv6 segment identifier list requirements on the chip processing capability and reduce the overhead in SRv6 networks.To improve the effective utilization of network bandwidth,and at the same time lay a solid foundation for the use of SRv6 network slicing,and promote the large-scale use of SRv6.